Mitochondrial Non-Coding RNAs Are Potential Mediators of Mitochondrial Homeostasis - Weihan Sun; Yijian Lu; Heng Zhang; Jun Zhang; Xinyu Fang; Jianxun Wang; Mengyang Li (Biomolecules, 2022)
Mitochondria are the energy production center in cells, which regulate aerobic metabolism, calcium balance, gene expression and cell death. Their homeostasis is crucial for cell viability. Although mitochondria own a nucleus-independent and self-replicating genome, most of the proteins, which fulfill mitochondrial functions and mitochondrial quality control, are encoded by the nuclear genome and are imported into mitochondria. Hence, the regulation of mitochondrial protein expression and translocation is considered essential for mitochondrial homeostasis. By means of high-throughput RNA sequencing and bioinformatic analysis, non-coding RNAs localized in mitochondria have been generally identified. They are either generated from the mitochondrial genome or the nuclear genome. The mitochondrial non-coding RNAs can directly interact with mitochondrial DNAs or transcripts to affect gene expression. They can also bind nuclear genome-encoded mitochondrial proteins to regulate their mitochondrial import, protein level and combination. Generally, mitochondrial non-coding RNAs act as regulators for mitochondrial processes including oxidative phosphorylation and metabolism. In this review, we would like to introduce the latest research progressions regarding mitochondrial non-coding RNAs and summarize their identification, biogenesis, translocation, molecular mechanism and function.